A study on the factors influencing the decisions of firms, companies and entrepreneurs to establish their businesses along Benigno Aquino Avenue, Jaro, West Mandurriao, Iloilo City - Causing, Erdith; Diocena, Richelle S.; Jandonero, Jane R.; Quimpo, Allan angelo L.; Tupas, Danny Q.; Villasoto, Mark Ian V.
Executive summary-Starting a business nowadays is a complex process especially for individuals considering putting up their own business. a number of activities like developing a business plan and project feasibility studies that help a businessman evaluate the viability of the business is usually conducted. Location is a crucial factor considered since it can make or break your business. some companies offering good products and/or services end up as a failure because of poor location. This paper aims to identify different factors that influence a businessman's decision to put up a business along Sen. Benigno Aquino Avenue, Jaro West Diversion Road, Mandurriao, Iloilo City. The study used various methods of data gathering such as book reviews, review of reading materials, interview among group of persons who have the expertise in the field of business, as well as Internet researches to suffice the study with the necessary information. Furthermore, questionnaires were distributed among entrepreneurs, companies, and firms along West Diversion road to obtain additional information which were basically that data used in the analysis of the study. The study made use of the descriptive and inferential statistical investigation and correlation, which is supported by the SPSS application program. After conduct of a thorough study, it was found out that the personal reason which motivated entrepreneurs, companies and firms to establish their business along West Diversion Road are mainly related to the accessibility of the area. The physical factors that most influenced the decisions of businessmen are parking considerations, and the possible Transportation costs. among the access factors, Access to Human Resources is the most considered. The economic factors that stood out the most are the Competition aspect, and Population density. In terms of government intervention with regard to the economic development of the diversion Road, it may be concluded that the government, specifically the local government of Iloilo City, is taking certain steps to develop the area. In fact it has designated West Diversion Road as a business/commercial area. It also has undertaken steps to provide better access to the area.